Work study on Thames Garment Industries - Cheung, Edison; Lam, Wai Pun; Sy, Jeaneth; Sy, Roger; Tan, Nelson (College of Engineering, 1988)
This project study was accomplished to implement the tools of work study, specifically methods study and work measurement. We used the set-up of a garment factory as our project site. We observed its day to day operations, identified the problem areas, evaluated the alternatives and we proposed the best solution. To accomplish our study, we physically observed the daily operations of the firm, thus gaining valuable first hand information. We recorded actual data like time and physical measurement of the factory. We also interviewed various personnel ranging from the chief operating officer to the sewers themselves. We tabulated our data using the different forms of method study like the flow process, outline process and time study chart. During the discussion we gave some alternative solutions, evaluated it and gave our recommendation which will improve the productivity of the firm.